2014
DOI: 10.1590/0004-282x20130190
|View full text |Cite
|
Sign up to set email alerts
|

Low specificity and sensitivity of smell identification testing for the diagnosis of Parkinson?s disease

Abstract: Objective: The aim of this study is to determine if the University of Pennsylvania's Smell Identification Test (UPSIT) is an accurate diagnostic tool for olfactory dysfunction in Parkinson's disease (PD). Method: We included 138 non-demented PD subjects and 175 control subjects matched by gender. Smell identification was tested using UPSIT. Results: The mean number of UPSIT items correctly identified by controls was 27.52±5.88; the mean score for PD subjects was 19.66±6.08 (p=<0.001). UPSIT sensitivity was 79.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
7
0
2
Order By: Relevance
“…In our sample, the optimal cut-off score was identified as ≤25, with a diagnostic accuracy of 82.7%, a sensitivity of 81.4%, and a specificity of 84.6%. This observed sensitivity is similar to that found in a Mexican population using the same cut-off score (Rodriguez-Violante, Gonzalez-Latapi, Camacho-Ordonez, et al, 2014a, 2014b. In an Italian study, the cut-off score of ≤21 differentiated PD and HC with similar sensitivity (82.0%) and specificity (88.2%) (Picillo et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our sample, the optimal cut-off score was identified as ≤25, with a diagnostic accuracy of 82.7%, a sensitivity of 81.4%, and a specificity of 84.6%. This observed sensitivity is similar to that found in a Mexican population using the same cut-off score (Rodriguez-Violante, Gonzalez-Latapi, Camacho-Ordonez, et al, 2014a, 2014b. In an Italian study, the cut-off score of ≤21 differentiated PD and HC with similar sensitivity (82.0%) and specificity (88.2%) (Picillo et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…We performed an item analysis similar to previous works (Kondo, Matsuda, Hashiba, 1998;Picillo et al, 2014;Rodriguez-Violante, Gonzalez-Latapi, Camacho-Ordonez, et al, 2014b;Silveira-Moriyama et al, 2008). Our results showed that some items had a rate of correct answers of less than 50.0% in HC (cedar, lemon, cherry, dill pickle and walnut), specifically, the three age groups coincided on dill pickle and walnut.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…47,48 Its utility as a diagnostic tool, however, is limited due to the low sensitivity and specificity of testing. 49 Pain is a frequent complaint among patients with PD, with one study estimating the prevalence at 83%. 28,50 Rapid eye-movement (REM) sleep behavior disorder, manifested by acting out dreams with a loss of normal atonia during REM sleep, can also predate the onset of motor symptoms by many years, or occur at any point during the disease.…”
Section: Nonmotor Featuresmentioning
confidence: 99%
“…Such testing is critical for assessing olfactory dysfunction, since self‐report can be unreliable 10. However, the only information typically retained from an UPSIT test – the total score – may be a crude measure for guiding diagnosis; while the mean total score of the PD subpopulation is lower than in healthy subjects,9 the sensitivity and specificity of the total score in distinguishing PD from non‐PD‐related olfactory deficits may not be high enough, or early enough in disease progression, to be clinically valuable 11. But what if the pattern of olfactory decline due to PD differs from that due to other age‐related pathologies or to normal aging?…”
Section: Introductionmentioning
confidence: 99%